2012
DOI: 10.1007/s00167-012-2129-9
|View full text |Cite
|
Sign up to set email alerts
|

Return to work and clinical outcome after open wedge HTO

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 29 publications
3
50
1
4
Order By: Relevance
“…One additional study reported that 89% of an homogeneous group of agricultural workers had returned to work after 8–12 months, but did not specify the exact timing [39]. Two studies found timing of RTW was significantly dependent on the workload, which was assessed using the REFA workload classification [25, 54]. Duration of inability to work varied from 6 and 10 weeks for REFA grade 0 (lowest workload) to 17 and 22 weeks for REFA 4 (heaviest physical strain) ( p  < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One additional study reported that 89% of an homogeneous group of agricultural workers had returned to work after 8–12 months, but did not specify the exact timing [39]. Two studies found timing of RTW was significantly dependent on the workload, which was assessed using the REFA workload classification [25, 54]. Duration of inability to work varied from 6 and 10 weeks for REFA grade 0 (lowest workload) to 17 and 22 weeks for REFA 4 (heaviest physical strain) ( p  < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, three studies adjusted for the effect of workload on RTW: two of these [25, 54] found that higher workloads resulted in longer inability to work, but one study [47] found no significant difference in RTW between high and low workloads. Only one study [34] compared RTW for different types of HTO; it found no significant difference in time to RTW between open- and closed-wedge HTO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The REFA-Classification is already used in knee surgery to describe changes in the workplace after operative intervention [33]. However, it is a useful instrument that should also be established in the cruciate ligament surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the KineSpring procedure, HTO involves significant bone removal and reshaping in an effort to shift loading from the diseased compartment to the unaffected compartment. The surgical invasiveness of HTO has been shown to require approximately 9 days of postoperative hospitalization, on average [19] as well as a substantial delay in return to work typically lasting 3 months with some patients incapacitated far longer [20]. Additionally, despite satisfactory early outcomes with HTO, patient outcomes reliably worsen over time [21].…”
Section: Discussionmentioning
confidence: 99%